Knowledge and adherence to iron and calcium supplementations during pregnancy. - Niroula,Karuna (2020)
EXECUTIVE SUMMARY: Background and Aim: This paper reviews the Knowledge and Adherence to iron and calcium during pregnancy among the pregnant women visiting the Paropakar women's and maternity hospital. The lack of iron and calcium during pregnancy causes iron deficiency anemia and preeclampsia respectively which has caused many maternal deaths in developing countries. Our study oversees the condition of maternal health in Nepal and the knowledge and adherence of the pregnant women on the iron and calcium supplements and diseases they cause and the effect it causes on the maternal health. The present study will be able to determine the association between level of adherence to iron and the status of hemoglobin and also level of adherence to calcium with high blood pressure. Methods: Data for this study is collected through a Structured Standardized Interview (face to face) with semi structured questionnaire. The questionnaire is based on Socio Demographic characteristics, health factors, Adherence to supplements and knowledge about supplements. Written informed consent was given to the participants prior to participating in the study. Haemoglobin concentration, Blood Pressure and level of protein in the urine was assessed based on the last medical records. Findings: The finding obtained through the study in many circumstance will be an asset to raise the awareness to these specific population regarding the knowledge and adherence and its importance so as to improve the maternal health and also to develop the new policies based on this study on the field of maternal health. Our study revealed that only 15% of the respondent were highly adherent to Iron. 32.3% of women had adequate knowledge about iron supplement and anemia Significant association between residence, education and adherence was observed. Age, gravidity , parity, frequency of ANC visit gestational age had no significant association with adherence to supplements. Significant association was observed between the level of hemoglobin and adherence to anemia. Conclusion: Adherence to iron and calcium supplement among women during pregnancy needs continuous improvement by proper distribution of supplements, proper counseling to patients and individualized message sharing.